PERSEPSI PENGGUNA TERHADAP KELEBIHAN DAN KELEMAHAN INDRIVER DALAM KONTEKS PERSAINGAN TRANSPORTASI ONLINE DI KOTA SURABAYA - Darjanto, Michael Stefanus (Seminar Nasional Ilmu Terapan, 2024)
This study aims to explore users' perceptions of the InDriver application, including its strengths and weaknesses, in the context of online transportation competition in Surabaya City. It adopts a qualitative descriptive field research approach. The primary data was gathered through interviews with seven InDriver users in Surabaya, selected using simple random sampling. Data collection methods included observation, interviews, and documentation. Data processing involved editing, classification, and interpretation, followed by descriptive analysis. The research findings indicate two main results. Firstly, users' perceptions of the InDriver application in Surabaya tend to be positive due to its price negotiation feature, driver selection options, and vehicle types, which provide greater flexibility compared to other online transportation services. Users appreciate the cost-effectiveness and additional value of the price negotiation feature. However, shortcomings such as the absence of non-cash payment methods and issues with order cancellations by drivers cause discomfort among users. Secondly, InDriver's primary advantage lies in its price negotiation feature, which allows users to negotiate and select drivers and vehicle types, thereby offering greater flexibility, control, and economic benefits. The ability to choose drivers based on ratings and vehicle types also enhances users' trust. However, there are drawbacks such as the lack of non-cash payment methods, inaccuracies in mapping or navigation, and instances of unfriendly and unprofessional driver behavior. These shortcomings diminish InDriver's competitiveness compared to other online transportation services.